Extracellular respiration - Gralnick, Jeffrey A; Newman, Dianne K (Molecular microbiology, 2007)
Although it has long been known that microbes can generate energy using diverse strategies, only recently has it become clear that a growing number involve electron transfer to or from extracellular substrates. The best-known example of what we will term 'extracellular respiration' is electron transfer between microbes and minerals, such as iron and manganese (hydr)oxides. This makes sense, given that these minerals are sparingly soluble. What is perhaps surprising, however, is that a number of substrates that might typically be classified as 'soluble' are also respired at the cell surface. There are several reasons why this might be the case: the substrate, in its ecological context, might be associated with a solid surface and thus effectively insoluble; the substrate, while soluble, might simply be too large to transport inside the cell; or the substrate, while benign in one redox state, might become toxic after it is metabolized. In this review, we discuss various examples of extracellular respiration, paying particular attention to what is known about the molecular mechanisms underlying these processes. As will become clear, much remains to be learned about the biochemistry, cell biology and regulation of extracellular respiration, making it a rich field of study for molecular microbiologists.